Quantifying lens obstructions in minimally invasive surgery: the impact on performance and outcomes - Łącki, Maciej; Kalia, Megha; Abraham, Nidhi; Vasudeva, Sukesh Adiga; Ko, Dicken S. C.; Bernard, Timothée; Lorincz, Amy (Frontiers in Surgery, 2025)
Surgeons performing laparoscopic surgery depend primarily on their vision to operate, but it often gets obstructed by fog, smoke, and other debris. This mini-review examines the literature on lens obstruction, aiming to quantify its prevalence, identify factors affecting its frequency, evaluate its impacts on surgeons and patients, and present an overview of mitigation methods. The review reveals that there are typically between 3.5–15 lens obstruction events per procedure, and surgeons spend between 19% and 52% of the procedure with suboptimal vision. Additionally, 2% to 8% of the operating time is devoted to cleaning the scope. Factors influencing the frequency of lens obstructions include instrument selection, operating time, and surgeon experience. Lens obstructions may increase operating time, the risk of medical errors, and mental fatigue, though quantifiable results on this subject remain sparse. The review also highlights significant knowledge gaps in the field of lens obstructions during minimally invasive procedures and proposes several recommendations to accelerate research in this area.